Morphophonemics in the Lamalera Dialect of Lamaholot - Yosef Demon (Randwick International of Education and Linguistics Science Journal, 2022)
Every language has differences and similarities in its linguistic systems. This is based on the assumption that the languages used by humans around the world come from one common ancestor. However, there are phenomena which are peculiar to each language. Morphophonemic alternation is a universal phenomenon. This means that all languages have this phenomenon. However, there are interesting peculiarities, for example, the morphophonemic alternations in agglutinative languages differ from isolating languages, tonal languages and inflecting languages. Lamaholot language is is not agglutinative, nor is it anlative (?) nor is it tonal. As a language characterized by neither agglutination, isolation nor tone, Lamaholot language has interesting morphophonemic phenomena to study. There is an elision or elimination of sounds, there is the addition or insertion of sounds, there is the preservation of sounds and certain sounds that are altered due to the addition of other sounds. This uniqueness occurs because Lamaholot Language does not have verb affixes as a strategy for morphophonemic change.